1985
DOI: 10.1055/s-2007-969471
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Relaxant Properties of Aqueous Extract ofLippia multiflora

Abstract: Aqueous leaf extracts of Lippia multiflora administered intraperitoneally produced a profound calming effect, muscle relaxing action, and significant reduction in the spontaneous locomotor activity of mice measured in the Ugo Basile activity cage. The extract (0.25-1.0 g kgj reduced amphetamine induced locomotor activity in mice. The extract (0.5-1.0 mg mt') inhibited contractions of the isolated rat diaphragm in response to the phrenic nerve stimulation. The muscle relaxant effect was considered to be primari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…The three preparations used in the toxicity study were presented to the mice at high concentration, thus the presence of xanthine may have over-stimulated the mice and led to a depressant phase without the typical initial stimulation phase with clonic convulsions, which is a rapid alternating contraction and relaxation of muscles. For instance, Noamesi et al (1985a) demonstrated tranquilizer and analgesic effects of L. multiflora in rats, similar to those of diazepam, after doses ranging from 200 to 1,200 mg/kg of L. multiflora lyophilisated powder obtained from an infusion of dried leaves dissolved in NaCl administered by either the intraperitoneal or oral route. In that experiment, the tranquilizer and analgesic phase was preceded by a precocious ataxic phase and the quality of the symptoms and signs observed were dose dependant unlike in the present study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The three preparations used in the toxicity study were presented to the mice at high concentration, thus the presence of xanthine may have over-stimulated the mice and led to a depressant phase without the typical initial stimulation phase with clonic convulsions, which is a rapid alternating contraction and relaxation of muscles. For instance, Noamesi et al (1985a) demonstrated tranquilizer and analgesic effects of L. multiflora in rats, similar to those of diazepam, after doses ranging from 200 to 1,200 mg/kg of L. multiflora lyophilisated powder obtained from an infusion of dried leaves dissolved in NaCl administered by either the intraperitoneal or oral route. In that experiment, the tranquilizer and analgesic phase was preceded by a precocious ataxic phase and the quality of the symptoms and signs observed were dose dependant unlike in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Xanthine is a demethylated derivative of caffeine with pharmacological actions such as central nervous system (CNS) stimulation, relaxation of smooth muscle (especially bronchial muscle), myocardial stimulation, peripheral vasoconstriction and diuresis. Lippia multiflora, a species found in many parts of sub-Saharan Africa, is also known to contain xanthine (Noamesi et al 1985a).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in an earlier investigation (3), that no evidence has been found to support a central nervous system activity of the extract that might influence its blood pressure lowering effect as was the case with regards to drugs like clonidine and alpha-methyldopa. However, in the same investigation (3) evidence was produced to support a skeletal muscle relaxant property for the extract.…”
Section: Resultsmentioning
confidence: 92%
“…The decoction has, in addition to the antihypertensive effect, been observed to produce a reduction in body tension similar to a tranquilizing effect. This effect, which has been investigated pharmacologically (3) was found to be as a result of a muscle relaxant property of the leaf extract.…”
Section: Introductionmentioning
confidence: 97%
“…Bouquet et Debray (1974) ont indiqué qu'elle est communément appelée «thé de savane» ou «thé de Gambie» et traditionnellement utilisée pour soigner les affections bronchiques, les accès fébriles, la rhinopharyngite, les conjonctivites et les ictères. De plus les travaux de Silou et al (1992) ont montré que le thé de savane est un hypotenseur qui présente des propriétés pesticides Noamesi et al (1985) ont rapporté que l'extrait aqueux des feuilles de L. multiflora possèdent un effet calmant. Dans les communautés rurales d'Afrique occidentale et centrale, Jim et al (2004) ont observé que le thé de Lippia multiflora consommé après les travaux champêtres permet une bonne détente et un sommeil réparateur.…”
Section: Introductionunclassified